2022
DOI: 10.1021/acsomega.2c06613
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanoplatelet/Multiwalled Carbon Nanotube/Polypyrrole Hybrid Fillers in Polyurethane Nanohybrids with 3D Conductive Networks for EMI Shielding

Abstract: This work reports the preparation of graphene nanoplatelet (GNP)/multiwalled carbon nanotube (MWCNT)/ polypyrrole (PPy) hybrid fillers via in situ chemical oxidative polymerization with the addition of a cationic surfactant, hexadecyltrimethylammonium bromide. These hybrid fillers were incorporated into polyurethane (PU) to prepare GNP/MWCNT/PPy/PU nanohybrids. The electrical conductivity of the nanohybrids was synergistically enhanced by the high conductivity of the hybrid fillers. Furthermore, the electromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Furthermore, the t value was 3.05, implying the formation of a three-dimensional network of CNTs and graphene. 64 Lin et al 65 incorporated GNP/CNT and polypyrrole hybrid fillers in polyurethane matrix. They reported high values of conductivity with higher amount of CNT/GNP, related to PPy, as expected, due to the higher conductivity.…”
Section: Samplesmentioning
confidence: 99%
“…Furthermore, the t value was 3.05, implying the formation of a three-dimensional network of CNTs and graphene. 64 Lin et al 65 incorporated GNP/CNT and polypyrrole hybrid fillers in polyurethane matrix. They reported high values of conductivity with higher amount of CNT/GNP, related to PPy, as expected, due to the higher conductivity.…”
Section: Samplesmentioning
confidence: 99%
“…The polymers were reinforced with carbon nanofiller-like graphene, graphene derivatives, and carbon nanotubes to improve the EMI shielding efficiency [158]. However, metal nanoparticles and inorganic nanofillers have also been reported as polymer reinforcements for EMI SE features [159,160]. In this context, it was essential to study and understand the mechanism of radiation shielding materials [161].…”
Section: Value Of Graphene Nanocomposites In Emi Shieldingmentioning
confidence: 99%
“…Lin et al showed that graphene exhibits a higher electron shielding effect than CNT. In addition, it was shown that when CNT and graphene were hybridized, electrical conductivity was improved by about eight times [ 22 ]. In previous research results, materials with a three-dimensional structure, compared to one-dimensional shielding materials, have higher electromagnetic wave shielding effects [ 23 ].…”
Section: Introductionmentioning
confidence: 99%